Nanoarchitectonics beyond perfect order – not quite perfect but quite useful. Issue 43 (24th October 2022) - Cao, Lin; Huang, Yanqi; Parakhonskiy, Bogdan; Skirtach, Andre G.
Abstract : Nanoarchitectonics, like architectonics, allows the design and building of structures, but at the nanoscale. Abstract : Nanoarchitectonics, like architectonics, allows the design and building of structures, but at the nanoscale. Unlike those in architectonics, and even macro-, micro-, and atomic-scale architectonics, the assembled structures at the nanoscale do not always follow the projected design. In fact, they do follow the projected design but only for self-assembly processes producing structures with perfect order. Here, we look at nanoarchitectonics allowing the building of nanostructures without a perfect arrangement of building blocks. Here, fabrication of structures from molecules, polymers, nanoparticles, and nanosheets to polymer brushes, layer-by-layer assembly structures, and hydrogels through self-assembly processes is discussed, where perfect order is not necessarily the aim to be achieved. Both planar substrate and spherical template-based assemblies are discussed, showing the challenging nature of research in this field and the usefulness of such structures for numerous applications, which are also discussed here.